Hybrid membrane bioreactor for biodegradation and biofouling reduction of palm oil mill effluent [electronic resource] - Alia Damayanti, 1977- author; Fakulti Kejuruteraan Awam (2011)
Thesis (Ph.D (Kejuruteraan Awam)) - Universiti Teknologi Malaysia, 2011